PERLINDUNGAN HUKUM TERHADAP PEREMPUAN KEKERASAN DALAM RUMAH T ANGGA - Anastasia Innutrisniyati (Fakultas Hukum Universitas Surabaya, 2018)
Domestic violence is a form violence against women that occurs continuously and dangerously, because of the violence has been prevalent for people in various countries. Patriarchal cultural factors, economic, gender, sexual, wrong understanding of religion, infidelity, jealousy, and other causes of violence against women in the household. Legal protection for women victims of domestic violence regulated in Act Number 7 of I 984, Act Number 39 of 1999, Act Number 23 of2004, and 1945 constitution amandment of paragraph 1 of Article 28G and paragraph 2 of Article 28H. However, the protection of the law for women victims of domestic violence will be hampered if the existing legal system has not been responsive to the interests of women.